Banahaw [videorecording] faith in nature, nature in faith - Medina, Susan Calo (Travel Time, 1995)
Features Mount Banahaw as the sacred and blessed mountain. It is a home to many religious cults like the Ciudad Mistica de Dios, Tres Persona Solo Dios and the Rizalistas.